Performance analysis of a residential photovoltaic string under partial shading - Byunggyu Yu; Youngseok Jung (International Journal of Electrical and Computer Engineering (IJECE), 2023)
As one of the most prominent renewable energy resources, Photovoltaic (PV) generation has been growing dramatically over the last years and its applications are classified into residential, commercial, and power plant class, based on its power capacity. Especially, a typical residential PV system has been configured with serially connected PV modules. For serially connected PV modules, shading is a critical factor to reduce the whole string PV output power. This paper presents study on performance analysis of a residential PV string under partial shading. This analysis contains how many maximum power points (MPPs) occur and how much power would be lost while a PV string is under partial shading with different shading positions and different shading intensities. PSIM simulation tool is used to verify the performance analysis. As a result, the number of MPPs is directly related with the number of shading intensities, regardless of the shading position. In this paper, it was verified that 8 maximum power points were generated for 8 solar intensities regardless of the location of the shadows under extreme conditions. These results can be utilized for fault diagnosis in the PV string.